Blast fire temperature exposure of geopolymer-based slurry infiltrated fibrous concrete - Balamurali Kanagaraj; Samuvel Raj R; Alin Joe; N. Anand; Eva Lubloy (Case Studies in Construction Materials)
Geopolymer concrete (GPC), developed using industrial by-products and activated with alkaline solutions, offers a sustainable alternative to conventional cement concrete. However, while concrete performs well under compressive loads, its tensile capacity remains limited. To overcome this limitation, the present study focuses on the development of high-volume fiber-reinforced geopolymer concrete using slurry infiltration techniques, forming slurry-infiltrated fibrous concrete (SIFCON). Two mix designs were investigated: (i) SIF-B, composed entirely of binder materials (fly ash and slag), and (ii) SIF-M, combining binder and fine filler materials. The residual mechanical performance of these mixes was evaluated under fire exposure conditions, following the ISO 834 heating curve at target temperatures of 821 °C, 925 °C, 986 °C, and 1029 °C. Key results show that after 120 min of exposure, SIF-M exhibited a residual compressive strength of 20.8 MPa (41 % strength loss), while SIF-B showed a strength of 28 MPa (51.7 % loss). Despite higher strength retention in SIF-B, SIF-M-2.36 demonstrated reduced crack width (0.45 mm vs 0.85 mm) and lower crack area (1750.5 mm² vs 2753 mm²), indicating better crack resistance. The flow diameter was also significantly higher for SIF-B (390 mm) compared to SIF-M-4.75 (306 mm) and SIF-M-2.36 (322 mm). Moreover, SIF-M showed lower porosity (2.57 %) and mass loss (13.3 %) than SIF-B (3.3 % and 17 %, respectively). Overall, the findings show that geopolymer-based SIFCON with optimized filler composition can improve fire resistance performance, flowability, and crack control, making it a promising material for high-performance, thermally stable concrete applications.